遊離腓骨皮弁による下顎再建 −過去, 現在, これから - 明石, 昌也; 楠元, 順哉 (日本口腔外科学会雑誌, 2023)
The free fibula osteocutaneous flap is currently the first-line option for mandibular reconstruction in the authors' department. There have been significant changes in plate fixation methods and preoperative evaluation, including donor side selection. In recent years, custom-made reconstruction methods based on computed tomographic methods have been introduced, including customization of the osteotomy site and reconstruction plate. The present article describes methods of mandibular reconstruction using the free fibula osteocutaneous flap performed in the authors' department to date, in addition to the problems encountered. The ensuing discussion address the utility of the custom-made reconstruction method. 　First, the process leading up to reconstruction surgery and the method of reconstruction was described, followed by a comparison of the types of plates used, their characteristics, and postoperative course. Plate types were classified as mini-, conventional reconstruction, and custom-made reconstruction. Cases involving the custom-made mandibular reconstruction method were presented in addition to a discussion of its utility. 　The current standard method in the authors' department was to manually bend the reconstruction plate to fit the model and fix it to the remaining mandible after shaving the area to be resected on the three-dimensional model. In many cases, no major problems, such as impaired postoperative function, have been encountered. In contrast, positioning was often difficult in patients undergoing hemi-mandibulectomy or median resection of the mandible. Although the authors' experience with custom-made mandibular reconstruction was limited, they have found it to be particularly useful in patients undergoing hemi-mandibulectomy or those requiring division of the fibula flap into multiple segments. 　The currently available custom-made reconstruction method was considered more useful for larger resection areas, but not as advantageous for defects as small as the mandibular body. Further advances and developments in digital technologies are anticipated, which will make custom-made mandibular reconstruction easier to perform in the future. In the meantime, however, it was considered necessary to improve the accuracy of the currently used conventional method through trial and error.